Reflections on the Asian Hotel Attributes: The Russian Gaze. Issue 3 (1st October 2016) - Tolkach, Denis; Tse, Tony S.M.
ABSTRACT: The current paper focuses on a lucrative, but a relatively unknown Russian market. Content analysis of online reviews from three review websites is conducted and the important hotel attributes for Russian visitors to Hong Kong are identified. The results demonstrate that Russian guests, as with other markets, place importance on scenic views, accessibility, breakfasts, swimming pools and friendly and attentive staff. Several issues that emerged in the current study merit further attention. Owing to high fluctuation of national currency exchange rates the mode and timing of payment is an important consideration. Experience of a room booking via an online travel agency may impact on the hotel experience. Hotel brand, Russian-speaking staff and Russian language information did not appear important.